Enhancing the conductivity of bacterial cellulose/polyvinyl alcohol composite for the development of flexible transparent electrodes - Diale, M. (Mmantsae Moche) (University of Pretoria, 2025)
Dissertation (MSc (Physics))--University of Pretoria, 2024.